All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 70818 by oyemi kemewari last updated on 08/Oct/19
whattheprovethat∫abf(x)dx=∫abf(a+b−x)dx
Commented by kaivan.ahmadi last updated on 08/Oct/19
u=a+b−x⇒du=−dx{x=a⇒u=bx=b⇒u=a⇒∫abf(a+b−x)dx=∫ba−f(u)du=∫abf(u)du=∫abf(x)dx
Answered by MJS last updated on 08/Oct/19
∫baf(x)dx=[F(x)]ab=F(b)−F(a)∫baf(a+b−x)dx=[t=a+b−x⇒dx=−dt]=−∫abf(t)dt=−[F(t)]ba=[F(t)]ab=F(b)−F(a)
Terms of Service
Privacy Policy
Contact: info@tinkutara.com